Magic realism: Mingling of fantasy and reality, tragedy and comedy in Gabriel Garcia Marquez's one hundred years of solitude and Salman Rushdie's Midnight's children - Sultana, Salma (BRAC University, 2010)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2009.